2020
DOI: 10.1093/botlinnean/boaa031
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the ancestral flowers of Ranunculales

Abstract: The question of the origin of petals has long been debated in the botanical literature. Ranunculales are characterized by a spectacular floral diversity, particularly at the perianth level. Recent progress in understanding the genetic bases of floral organ identity suggests a single origin for petals in Ranunculaceae, contrasting with the traditional morphological hypothesis of repeated evolution. However, perianth evolution at the ordinal level remains incompletely understood. Recent advances in the elucidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 91 publications
0
16
0
Order By: Relevance
“…Thus, reconstruction of the ancestral gynoecium condition in a clade of all angiosperms except Amborella is directly sensitive to the unstable placement of Nuphar . Two families–the apocarpous Eupteleaceae (single genus Euptelea ) and the syncarpous Papaveraceae–are unresolved at the root of the basal eudicot lineage Ranunculales ( Carrive et al, 2020 ). Similarly, two families with contrasting gynoecium morphology (Tofieldiaceae and Araceae) are unresolved at the root of Alismatales, a lineage of basal monocots ( Luo et al, 2016 ; Ross et al, 2016 ; Givnish et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, reconstruction of the ancestral gynoecium condition in a clade of all angiosperms except Amborella is directly sensitive to the unstable placement of Nuphar . Two families–the apocarpous Eupteleaceae (single genus Euptelea ) and the syncarpous Papaveraceae–are unresolved at the root of the basal eudicot lineage Ranunculales ( Carrive et al, 2020 ). Similarly, two families with contrasting gynoecium morphology (Tofieldiaceae and Araceae) are unresolved at the root of Alismatales, a lineage of basal monocots ( Luo et al, 2016 ; Ross et al, 2016 ; Givnish et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…Jabbour et al unpublished manuscript). Because nectariferous petals originated once within Ranunculaceae (Carrive et al 2020), petals in Nigelleae and Delphinieae are homologous.…”
Section: Samplingmentioning
confidence: 99%
“…In Ranunculales, the earliest-diverging order of eudicots (APG IV 2016), synorganization was briefly reported in the flowers of the tribe Delphinieae, in which the nectar spurs of the dorsal petals are nested within the hollow dorsal sepal (Chartier et al 2016;Chen et al 2018;Jabbour et al in press). The phylogenetic position of Delphinieae within Ranunculaceae, and the floral morphological evolution in the family were both clarified recently (Zhai et al 2019;Carrive et al 2020). Phylogenetic relationships within Delphinieae have been largely clarified as well in the last ten years Renner 2011b, 2012b;Wang et al 2013;Espinosa et al 2017;Hong et al 2017;Xiang et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The order Ranunculales is among the most diverse angiosperm lineages with respect to floral organization ( Carrive et al, 2020 ). The flowers display considerable variation in terms of number of floral organs, size, organ shape, and perianth differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, petals in Ranunculaceae were considered to have been repeatedly recruited from stamens during the evolutionary history of the family ( Kosuge, 1994 ; Ronse De Craene, 2007 ). This view has recently been challenged by evo-devo studies of ABCE model gene expression in several Ranunculales species (reviewed in Damerval and Becker, 2017 ; Meaders et al, 2020 ) and by the Ranunculales-wide study on flower organization of Carrive et al (2020) . These studies revealed that the ancestral flower of Ranunculaceae likely had petals that were further lost repeatedly in several genera belonging to different tribes ( Anemone, Anemoclema, Enemion, Clematis, Caltha, Glaucidium, Hydrasti s).…”
Section: Introductionmentioning
confidence: 99%